Earth observation for quantifying ecohydrological fluxes & interrelations :A regional case: The Konya Closed Basin, Turkey - Verhoef, W. (University of Twente Faculty of Geo-Information and Earth Observation (ITC), 2020)
PhD thesis Univesity of Twente, Summary in English